2012
DOI: 10.1377/hlthaff.2011.0653
|View full text |Cite
|
Sign up to set email alerts
|

Massachusetts Health Reforms: Uninsurance Remains Low, Self-Reported Health Status Improves As State Prepares To Tackle Costs

Abstract: The Massachusetts health reform initiative enacted into law in 2006 continued to fare well in 2010, with uninsurance rates remaining quite low and employer-sponsored insurance still strong. Access to health care also remained strong, and first-time reductions in emergency department visits and hospital inpatient stays suggested improvements in the effectiveness of health care delivery in the state. There were also improvements in self-reported health status. The affordability of health care, however, remains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 2 publications
4
88
0
Order By: Relevance
“…2 Some early data from Massachusetts suggested that health insurance reform was associated with improvements in costrelated barriers to care but no improvements in access to a personal physician or health status. 3 Other evidence has demonstrated sustained improvements in access to a usual source of care and receipt of preventive care as well as gains in the affordability of health care 4,5 and improvements in health status, 6 although some patients still report challenges with access and affordability. 4,5 Women without insurance are less likely than the insured to receive preventive care, including mammograms, to seek care in a timely fashion, or to receive recommended treatment; and uninsured women are more likely to be diagnosed with breast cancers at a more advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…2 Some early data from Massachusetts suggested that health insurance reform was associated with improvements in costrelated barriers to care but no improvements in access to a personal physician or health status. 3 Other evidence has demonstrated sustained improvements in access to a usual source of care and receipt of preventive care as well as gains in the affordability of health care 4,5 and improvements in health status, 6 although some patients still report challenges with access and affordability. 4,5 Women without insurance are less likely than the insured to receive preventive care, including mammograms, to seek care in a timely fashion, or to receive recommended treatment; and uninsured women are more likely to be diagnosed with breast cancers at a more advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…19 In another study the percentage of adults ages 19-64 with a dental visit increased by five percentage points from 2006 to 2010. 20 Among adults ages 19-64 with incomes below 300 percent of poverty, the percentage with a dental visit in the past twelve months increased by 10.9 percentage points from 2006 to 2010. 21 Using National Health Interview Survey data from the period 2003-08, Sharon Long and Karen Stockley assessed the impact of Massachusetts's health reform by comparing dental care use among the state's nonelderly population and a subpopulation of nonelderly adults with family income below 300 percent of poverty to that of a control population of higher-income adults in the same region (New Jersey, New York, and Pennsylvania), higher-income adults in large states (Alabama, Arizona, California, Colorado, Florida, Georgia, Illinois, Indiana, Louisiana, Maryland, Michigan, Minnesota, Missouri, New Jersey, New York, North Carolina, Ohio, Pennsylvania, South Carolina, Tennessee, Texas, Virginia, Washington, and Wisconsin), and childless adults with family income below 300 percent of poverty in another set of large states (Alabama, Illinois, Missouri, North Carolina, South Carolina, Texas, and Wisconsin).…”
mentioning
confidence: 99%
“…Researchers have studied the effects of these coverage changes on a variety of outcomes and have found that they led to increases in health (Courtemanche and Zapata 2014;Long, Stockley, and Dahlen 2012), decreases in emergency room visits (Kolstad and Kowalski 2012b;Miller 2012), decreases in nongroup premiums (Graves and Gruber 2012), and increases in preventative services (Kolstad and Kowalski 2012b).…”
Section: Background On Health Reforms the Massachusetts Health Reformsmentioning
confidence: 99%